Traditional archery from six continents the Charles E. Grayson Collection - Grayson, Charles E., 1910- (University of Missouri Press, 2007)
"An overview of one of the largest and most comprehensive collections of European and non-European archery-related materials in the world. This book presents color photos and descriptions of some 300 items - including bows, arrows, quivers, and thumb rings- that represent traditional archery techniques, practices, and customs from around the world"--Provided by publisher.